Contribution to the knowledge of continental ostracod from Chile - Cardenas, Javiera (2013)
Our knowledge of continental ostracods in South America is still in its infancy with a total of only 260 species (MARTENS & BEHEN, 1994). Particularly in Chile, it is still scarce and scattered, with large voids in the taxonomy and distribution. In Chile, the first records were reported by DADAY (1902), BREHM (1934) and LÖFFLER (1961a, b). Later, SCHWALB & BURNS (1999) cited species of Limnocytheridae and KARANOVIC (2012) provided new records of Candonidae from Chile. The main objective of this work is to provide a checklist of ostracods in Chile with updated distributional records.